2017
DOI: 10.1111/resp.13093
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and asthma control level in children and adolescents

Abstract: No associations were observed between physical activity and asthma control level, spirometric measurements and quality of life in children and adolescents with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
3
21
1
3
Order By: Relevance
“…However associations between disease severity, medication prescription, and clinical symptoms are complex since loss of symptom control can occur, because of under‐prescribing, poor inhaler technique, nonadherence to medication, or severe or treatment‐resistant disease. Studies which have compared physical activity in children with severe or poorly controlled asthma to that in those with the less severe or well‐controlled disease have reported conflicting results; some have found reduced physical activity in association with more severe disease, or poorer control, while others have found no association . It is possible that previous hospital admission is a stronger influence upon physical activity than measures of medication or symptoms because it is a strong predictor of future attacks and this is something children with asthma (and their parents) wish to avoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However associations between disease severity, medication prescription, and clinical symptoms are complex since loss of symptom control can occur, because of under‐prescribing, poor inhaler technique, nonadherence to medication, or severe or treatment‐resistant disease. Studies which have compared physical activity in children with severe or poorly controlled asthma to that in those with the less severe or well‐controlled disease have reported conflicting results; some have found reduced physical activity in association with more severe disease, or poorer control, while others have found no association . It is possible that previous hospital admission is a stronger influence upon physical activity than measures of medication or symptoms because it is a strong predictor of future attacks and this is something children with asthma (and their parents) wish to avoid.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies have examined objective measures of physical activity or sedentary time in relation to asthma in a large nationally representative sample. Moreover, only a few studies have considered asthma severity or symptom control in relation to physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Holderness et al 35 found that, among the 324 children studied, there was a significant correlation between the level of asthma control and physical activity, with children having uncontrolled asthma reporting less physical activity than their peers who had mild asthma or no asthma. However, Matsunaga et al 36 found no such correlation in a population of 100 children studied. A meta-analysis of 8 cross-sectional and 1 longitudinal study using data from accelerometry demonstrated no significant difference in physical activity levels between children with and without asthma; however, our study used pedometers as opposed to accelerometers, the former of which do not measure exercise intensity.…”
Section: Discussionmentioning
confidence: 88%
“…reported that high bronchodilator response as well as high FeNO levels were associated with increased risk for loss of asthma control among children with atopic asthma. By comparison, Matsunaga et al . assessed the effect of physical activity on asthma control in children and adolescents aged 7–17 years with a diagnosis of atopic asthma, and found no association between physical activity, asthma control level, spirometric measurements and quality of life.…”
Section: Asthmamentioning
confidence: 99%
“…58 In addition, Kim et al 59 reported that high bronchodilator response as well as high FeNO levels were associated with increased risk for loss of asthma control among children with atopic asthma. By comparison, Matsunaga et al 60 assessed the effect of physical activity on asthma control in children and adolescents aged 7-17 years with a diagnosis of atopic asthma, and found no association between physical activity, asthma control level, spirometric measurements and quality of life. Among asymptomatic children, Habukawa et al 61 reported that a recently developed technology for analysing lung sounds using ic700 (index of chest wall at 700 Hz, sound intensity at 700 Hz) was useful in assessing the effects of ICS treatment, identifying those at high risk for asthma attack and predicting attack symptoms.…”
Section: Paediatric Asthmamentioning
confidence: 99%